High-concentration erbium-doped high-brightness optical communication waveband silicon-based light-emitting film and preparation method thereof
The preparation of erbium-doped silicon-rich silicon oxide films through sol-gel process and spin coating technology has solved the problem of quenching center residues and silicon nanocrystals in the film in the prior art, and achieved silicon-based luminescence with high brightness and high light gain film.
Patent Information
- Application Number
- CN202411508064.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-28
Smart Images

Figure CN119463690A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optical communication, and in particular relates to a silicon-based luminescent film and a preparation method thereof. Background Art
[0002] An ideal on-chip integrated light source for optical communication should have an emission wavelength of about 1310nm or 1550nm so that it can be connected to a fiber optic network. Rare earth ions, due to their unique electronic structure, form a rich energy level that can generate radiation or absorption from ultraviolet to infrared. Among them, the radiation transition wavelength of erbium ions is around 1550nm, which corresponds to the minimum loss window of optical fiber communication. At the same time, the luminescence lifetime is long, and it is easy to achieve population inversion. Studies have found that erbium ions doped in crystalline silicon can exhibit sharp, atomic-like, and temperature-independent radiation transitions, which can combine the good electrical properties of silicon with the excellent optical properties of rare earth ions to realize silicon-optical integrated light sources in the optical communication band.
[0003] Since Ennen et al. first realized the luminescence of erbium-doped silicon at a wavelength of 1.54μm in 1983, erbium-doped silicon-based luminescence systems have been widely, systematically and deeply studied. At present, there are two common erbium-doped silicon-based luminescent material systems, namely, erbium-doped bulk silicon and erbium-doped silicon-rich silicon oxide. Compared with the former, since the solid solubility of erbium ions in the silicon dioxide matrix is more than two orders of magnitude higher than that in bulk silicon, and the energy gap of silicon nanocrystals is larger than that of crystalline silicon, this will lead to an increase in the excitation energy required for erbium ion de-excitation to form bound excitons, and a decrease in the free carrier concentration, which can effectively inhibit the temperature quenching caused by energy back transfer and Auger recombination. Therefore, the erbium-doped silicon-rich silicon oxide system has a higher application prospect. In addition, the silicon nanocrystals in the erbium-doped silicon-rich silicon oxide film act as sensitizers and can transfer the absorbed energy to nearby erbium ions, sensitizing them to emit light. At the same time, the absorption cross-section of silicon nanocrystals is more than four orders of magnitude higher than that of erbium ions, and can absorb a continuous spectrum, thereby greatly improving the luminescence efficiency of erbium ions and reducing the requirements for the excitation light source.
[0004] Traditional methods for preparing erbium-doped silicon-rich silicon oxide thin films include sol-gel method, magnetron multi-target co-sputtering method, electron beam evaporation method and ion implantation method. In the silicon-rich silicon oxide thin films prepared by sol-gel method, there are a large number of serious quenching center hydroxyl groups and other residues, which make the luminescence weak; in the thin films prepared by magnetron multi-target co-sputtering method and electron beam evaporation method, the silicon nanocrystals formed after high-temperature annealing are large and uneven in size, dispersed in distribution and small in number. Since the energy transfer efficiency between silicon nanocrystals and erbium ions is inversely proportional to the sixth power of the distance between the two, it is extremely unfavorable for energy transfer between silicon nanocrystals and erbium ions; and in the process of ion implantation, the high-speed ions collide with the semiconductor lattice, which will produce a large number of point defects and lattice damage, resulting in non-ignorable luminescence quenching.
[0005] The present invention proposes a sol-gel process combined with spin coating technology to prepare a new type of erbium-doped silicon-rich silicon oxide silicon-based luminescent film. The method of using erbium nitrate pentahydrate crystals to directly dissolve in hydrogenated silsesquioxane (HSQ for short) avoids the generation of a large number of hydroxyl groups in the film, and at the same time has a higher solubility of erbium ions; and the silicon nanocrystals in the film have the characteristics of uniform size, uniform distribution, and large number, which is conducive to the occurrence of the energy transfer process, so that the concentration of optically active erbium ions in the film is greatly improved; in addition, by introducing ytterbium ions and co-doping with silicon quantum dot colloids, a high-brightness erbium-doped silicon-based luminescent film with superior photoluminescence performance and excellent optical gain is obtained. Summary of the invention
[0006] The object of the present invention is to provide a silicon-based luminescent film in an optical communication band with high erbium doping concentration, excellent luminescent performance and simple preparation process and a preparation method thereof.
[0007] The method for preparing a silicon-based luminescent film provided by the present invention uses hydrogenated silsesquioxane (HSQ for short) photoresist as a solvent, uses erbium nitrate pentahydrate as a source of erbium element, and co-dopes ytterbium ions and independent silicon quantum dots, and obtains a high-brightness erbium-doped silicon-based luminescent film after stirring, spin coating, and high-temperature annealing. The specific steps are as follows:
[0008] (1) Selecting a single-side polished silicon wafer as a substrate and cleaning and removing impurities on the substrate surface;
[0009] (2) adding erbium nitrate pentahydrate crystals, ytterbium nitrate pentahydrate crystals and silicon quantum dot colloid to HSQ, and stirring at room temperature until they are completely dissolved to form a mixed sol; wherein the mass of the erbium nitrate pentahydrate crystals is 0.4 g to 0.5 g, the mass of the ytterbium nitrate pentahydrate crystals is 0.1 g to 0.2 g, the volume of the silicon quantum dot colloid is 0.5 to 3 mL, the volume of the HSQ photoresist is 2 to 4 mL, and the stirring time is 45 min to 60 min;
[0010] (3) spin coating an erbium-doped HSQ mixed sol on a substrate to form an erbium-doped HSQ thin film;
[0011] (4) placing the erbium-doped HSQ film on a constant temperature drying machine for heating and curing;
[0012] (5) The cured erbium-doped HSQ film is placed in the central constant temperature zone of a tubular resistance furnace, and a mixed gas of N2 and H2 is introduced. The temperature of the tubular resistance furnace is raised from room temperature to 1050°C to 1100°C for 100 min to 120 min, and the temperature is maintained for 30 to 120 min.
[0013] Further:
[0014] In step (1), the silicon substrate used is P-type silicon, with a size of 20 mm×20 mm, a thickness of 525±25 μm, and a resistivity of 0.1 Ω·cm to 0.2 Ω·cm.
[0015] In step (1), the cleaning removes impurities on the surface of the substrate. Specifically, the silicon substrate is cleaned at 200 to 400° C. using a mixed solution of analytical pure concentrated sulfuric acid and 30% hydrogen peroxide solution for 90 min to 120 min. After cooling, the silicon substrate is rinsed alternately with anhydrous ethanol and deionized water, and then blown dry with a high-purity nitrogen gun.
[0016] In step (2), the silicon quantum dot colloid is extracted and synthesized using triethoxysilane as a precursor, and the specific operation process is as follows:
[0017] a. Add hydrochloric acid solution dropwise into 10 mL of triethoxysilane under argon atmosphere, stir and hydrolyze at room temperature to form a white jelly-like gel, and connect a sodium hydroxide washing bottle to remove the remaining hydrogen chloride gas;
[0018] b. Place the white jelly-like gel in a vacuum drying oven for 5h to 6h to dry it into a white solid, and then grind it into a white powder in a mortar;
[0019] c. Place the white powder in a quartz boat, push the quartz boat into the central constant temperature zone of the tubular resistance furnace, introduce H2:N2 mixed gas for high temperature annealing, and obtain a reddish brown powder, wherein the temperature is set as follows: the tubular resistance furnace is heated from room temperature to 1050°C to 1100°C, the heating time is 60min to 100min, and maintained at this temperature for 30 to 120min; then naturally cooled to 200 to 650°C, the cooling time is 2h to 3h, and the quartz boat is pulled out;
[0020] d. Use a ball mill to finely grind the reddish-brown powder to obtain silicon nanocrystalline fine powder. The ball milling parameters are set as follows: speed 400 to 700 rpm, duration 4 to 15 h;
[0021] e. Add 25 to 60 mL of a mixed solution of deionized water, anhydrous ethanol and 49% hydrofluoric acid in a volume ratio of 1:1:1 to 1:1:4 to the silicon nanocrystal fine powder, and stir continuously at room temperature to etch the silicon nanocrystals and reduce the size of the silicon nanocrystals;
[0022] f. Add 10 to 20 mL of a mixed solution of 1-dodecene and mesitylene in a volume ratio of 3:8 to 5:8 to the etched silicon nanocrystal powder, and perform hydrosilylation in an argon environment to obtain a clear yellow solution at a temperature of 160 to 180° C. for 1 to 4 h;
[0023] g. Use anhydrous ethanol and methanol to wash away the residual 1-dodecene and trimethylbenzene in the clear yellow solution, and add n-pentane to obtain a uniformly dispersed silicon quantum dot colloid.
[0024] In step (3), the operation of spin coating the erbium-doped HSQ mixed sol is as follows: take 100 μL to 150 μL of the erbium-doped HSQ mixed sol, and set the spin coating parameters as follows: the first stage speed is 300 to 600 rpm, and the duration is 2 to 5 s; the second stage speed is 2000 to 4000 rpm, and the duration is 5 to 15 s.
[0025] In step (4), the erbium-doped HSQ film is placed on a constant temperature drying machine for heating and curing, the temperature of the constant temperature drying machine is 60 to 150° C., and the time is 5 to 20 minutes.
[0026] In step (5), the content of H2 in the mixed gas used is 1% to 10%.
[0027] The present invention uses HSQ photoresist as a precursor material for preparing a silicon nanocrystal film, and after doping with erbium elements and annealing at high temperature, the formed film contains a large amount of silicon nanocrystals. The silicon nanocrystals serve as a sensitizer in the energy transfer process, and absorb the energy of incident photons and then transfer and activate erbium ions. That is, the present invention utilizes the silicon nanocrystals embedded in the silicon dioxide matrix to absorb the energy of 300nm to 500nm light, and transfers it to the erbium ions around the silicon nanocrystals, so as to achieve photoluminescence with the erbium ion luminescence center located at 1.54μm. Since the number of quenching center hydroxyls of the film prepared by the present invention is small, the silicon nanocrystals are uniform in size, evenly distributed and large in number, the concentration of optically active erbium ions is high, and the photoluminescence performance is excellent.
[0028] The method of the present invention is different from the traditional ion implantation and magnetron sputtering erbium-doped silicon-based film preparation method, avoids a large number of defects caused by the ion implantation method, and does not need to maintain a high vacuum degree. The prepared erbium-doped film has the characteristics of high doping concentration and high concentration of silicon nanocrystals as erbium luminescence sensitizer. The above characteristics lead to a higher optical gain of the film in the optical communication band. Compared with erbium-doped silicon-rich films prepared by other methods, the optical gain is 1 to 2 orders of magnitude higher, and the preparation steps are simple and the operation is safe. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the structure of the erbium-doped silicon-based light-emitting film of the present invention.
[0030] Figure 2 The figure is a transmission electron microscope (TEM) image of silicon nanocrystals in the erbium-doped silicon-based light-emitting film of the present invention, and the inset is a high-magnification transmission electron microscope (HRTEM) image.
[0031] Figure 3 This is a histogram of the particle size distribution of silicon nanocrystals in the erbium-doped silicon-based luminescent film of the present invention.
[0032] Figure 4 This is the photoexcitation (PL) spectrum of the erbium-doped silicon-based luminescent film of the present invention under 405nm laser excitation.
[0033] Figure 5 This is a fitting curve diagram of the optical net gain measured under 405nm laser excitation of the erbium-doped silicon-based luminescent film of the present invention. DETAILED DESCRIPTION
[0034] The present invention is further described below by way of examples in conjunction with the accompanying drawings, but is not intended to limit the present invention.
[0035] 1. Raw materials and formula
[0036] Substrate: single-side polished single crystal (100) P-type silicon wafer, resistivity 0.1Ω·cm~0.2Ω·cm, size 20mm×20mm, thickness 525±25μm;
[0037] Substrate cleaning solution: concentrated sulfuric acid (analytical grade), 30% hydrogen peroxide, anhydrous ethanol, Sinopharm Chemical Reagent Co., Ltd.;
[0038] Raw materials: Erbium nitrate pentahydrate (analytical grade), Ytterbium nitrate pentahydrate (analytical grade), Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0039] Precursor materials: Hydrogenated silsesquioxane, Xuzhou Bokang Information Chemicals Co., Ltd.; triethoxysilane (analytical grade), Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0040] Hydrolysis solution: hydrochloric acid (analytical grade), Sinopharm Chemical Reagent Co., Ltd.;
[0041] Etching solution: 49% hydrofluoric acid, anhydrous ethanol, Sinopharm Chemical Reagent Co., Ltd.;
[0042] 2. Process parameter setting
[0043] Spin coating conditions: room temperature, clean environment;
[0044] Annealing temperature: 1100℃;
[0045] Annealing gas flow rate: 200sccm;
[0046] Annealing time: 60min;
[0047] Cooling parameters after annealing: After power off, the tube is cooled with the furnace at room temperature for 90 minutes;
[0048] 3. Production equipment
[0049] VD650 Clean Bench, Suzhou Su Clean Chemical Equipment Co., Ltd.
[0050] LS-1D Magnetic Stirrer, Azov (Shanghai) Trading Co., Ltd.
[0051] KW4A desktop glue machine, Institute of Microelectronics, Chinese Academy of Sciences
[0052] 200-00A Constant Temperature Drying Oven, Huxin Electric Furnace Electric Box Factory
[0053] SK2-2-12 program-controlled tubular resistance furnace, Shanghai Shiyan Circuit Co., Ltd.
[0054] Vertical Planetary Ball Mill, Changsha Deke Instrument Equipment Co., Ltd.
[0055] L550 desktop low speed centrifuge, Hunan Xiangyi Centrifuge Instrument Co., Ltd.
[0056] 4. Process
[0057] (1) Select a single-sided polished P-type silicon wafer with a resistivity of 0.1 Ω·cm to 0.2 Ω·cm, a size of 20 mm×20 mm, and a thickness of 525±25 μm and a (100) crystal orientation;
[0058] (2) Soak the silicon wafer in a mixed solution of analytical grade concentrated sulfuric acid and 30% hydrogen peroxide in a volume ratio of 1:1, heat at 290°C for 120 min, and after natural cooling, alternately ultrasonically rinse with deionized water and anhydrous ethanol, and then blow dry with a high-purity nitrogen gun for later use;
[0059] (3) under an argon environment, the hydrochloric acid solution was dripped into 10 mL of triethoxysilane, and the mixture was stirred and hydrolyzed at room temperature until a white jelly-like gel was formed, and a sodium hydroxide washing bottle was connected to remove the remaining hydrogen chloride gas;
[0060] (4) Place the white jelly-like gel in a vacuum drying oven for 5.5 h to dry it into a white solid, and then grind it into a white powder in a mortar;
[0061] (5) The white powder was placed in a quartz boat, and the quartz boat was pushed into the central constant temperature zone of a tubular resistance furnace, and a mixed gas of H2:N2 with a volume ratio of 5%:95% was introduced for high temperature annealing to obtain a reddish brown powder, wherein the temperature was set as follows: the tubular resistance furnace was heated from room temperature to 1100°C for 90 min, and maintained at this temperature for 90 min; then naturally cooled to 500°C, and the cooling time was 2 h, and the quartz boat was pulled out;
[0062] (6) Grinding the reddish brown powder using a ball mill to obtain silicon nanocrystal fine powder, with the ball milling parameters set as follows: speed 600 rpm, duration 10 h;
[0063] (7) adding 30 mL of a mixed solution of deionized water, anhydrous ethanol and 49% hydrofluoric acid in a volume ratio of 1:1:1 to the silicon nanocrystal fine powder, and stirring continuously at room temperature to etch the silicon nanocrystals and reduce the size of the silicon nanocrystals;
[0064] (8) adding 11 mL of a mixed solution of 1-dodecene and mesitylene in a volume ratio of 3:8 to the etched silicon nanocrystal powder, and performing hydrosilylation in an argon environment to obtain a clear yellow solution at a temperature of 165 ° C for 3 h;
[0065] (9) using anhydrous ethanol and methanol to wash away the residual 1-dodecene and trimethylbenzene in the clear yellow solution, and adding n-pentane to obtain a uniformly dispersed silicon quantum dot colloid;
[0066] (10) 0.4 g of erbium nitrate pentahydrate crystals, 0.2 g of ytterbium nitrate pentahydrate crystals, and 1 mL of the silicon quantum dot colloid prepared above were placed in 2 mL of HSQ, placed on a magnetic stirrer and stirred at 300 rpm at room temperature for 45 min until the solid was completely dissolved to form a clear pink sol;
[0067] (11) The cleaned silicon substrate was placed on the tray of the spin coating machine, and 150 μL of the Er-doped HSQ mixed sol was dropped on the substrate surface. The spin coating parameters were set as follows: the first stage speed was 500 rpm and the duration was 3 s; the second stage speed was 3000 rpm and the duration was 10 s;
[0068] (12) The spin-coated film sample was placed on a constant temperature drying machine to bake and solidify the film at a temperature of 80°C for 10 min;
[0069] (13) After the baked sample is cooled to room temperature, it is placed on a cleaned quartz substrate and pushed into the central constant temperature zone of a tubular resistance furnace. A mixed gas of H2:N2=5%:95% is introduced, and the mixed gas flow rate is 200sccm. The tubular resistance furnace is set to rise from room temperature to 1100°C, and the heating time is 100 min. The temperature is maintained at 1100°C for 60 min, and then the power is turned off. The sample is taken out after cooling in the furnace for 90 min.
[0070] Results and Analysis
[0071] By specific embodiments, such as Figure 1 As shown in FIG. 1 , a highly concentrated erbium-doped silicon-based luminescent film in the optical communication band was successfully prepared on a silicon substrate; Figure 2 Shown is a transmission electron microscope image of the prepared film, which shows that the film contains uniformly distributed silicon nanocrystals; Figure 3 The silicon nanocrystals in the film were counted and the size of the silicon nanocrystals in the film was found to be 2.89±0.14nm, with uniform size. Figure 4As shown in the figure, when the sample is excited by the non-resonant excitation light of erbium ions at 405 nm, strong erbium ion photoluminescence is observed at 1.54 μm. The optical net gain is tested by the variable aperture length-moving excitation point (VSL-SES) method, as shown in the figure. Figure 5 As shown in Figure 2, the optical net gain at 1.54 μm is 272 cm -1 or 24.35dB cm -1 , which is the highest optical net gain at 1.54μm reported so far among erbium-doped silicon-rich silicon oxide films.
Claims
1. A method for preparing a silicon-based light-emitting film, characterized in that: Using HSQ photoresist as solvent, erbium nitrate pentahydrate as the source of erbium element, and co-doping with ytterbium ions and independent silicon quantum dots, stirring, spin coating, and high-temperature annealing, a high-brightness erbium-doped silicon-based light-emitting film is obtained. The specific steps are as follows: (1) Selecting a single-side polished silicon wafer as a substrate and cleaning and removing impurities on the substrate surface; (2) adding erbium nitrate pentahydrate crystals, ytterbium nitrate pentahydrate crystals and silicon quantum dot colloid to HSQ, and stirring at room temperature until they are completely dissolved to form a mixed sol; wherein the mass of the erbium nitrate pentahydrate crystals is 0.4 g to 0.5 g, the mass of the ytterbium nitrate pentahydrate crystals is 0.1 g to 0.2 g, the volume of the silicon quantum dot colloid is 0.5 to 3 mL, the volume of the HSQ photoresist is 2 to 4 mL, and the stirring time is 45 min to 60 min; (3) spin coating an erbium-doped HSQ mixed sol on a substrate to form an erbium-doped HSQ thin film; (4) placing the erbium-doped HSQ film on a constant temperature drying machine for heating and curing; (5) The cured erbium-doped HSQ film is placed in the central constant temperature zone of a tubular resistance furnace, and a mixed gas of N2 and H2 is introduced. The temperature of the tubular resistance furnace is raised from room temperature to 1050°C to 1100°C for 100 min to 120 min, and the temperature is maintained for 30 to 120 min.
2. The preparation method according to claim 1, characterized in that: The cleaning in step (1) removes impurities on the surface of the substrate. Specifically, the silicon substrate is cleaned at 200 to 400° C. using a mixed solution of analytical grade concentrated sulfuric acid and 30% hydrogen peroxide solution for 90 to 120 minutes. After cooling, the silicon substrate is rinsed alternately with anhydrous ethanol and deionized water, and then blown dry with a high-purity nitrogen gun.
3. The preparation method according to claim 1, characterized in that: The silicon quantum dot colloid described in step (2) is extracted and synthesized using triethoxysilane as a precursor, and the specific operation process is as follows: a. Add hydrochloric acid solution dropwise into 10 mL of triethoxysilane under argon atmosphere, stir and hydrolyze at room temperature to form a white jelly-like gel, and connect a sodium hydroxide washing bottle to remove the remaining hydrogen chloride gas; b. Place the white jelly-like gel in a vacuum drying oven for 5h to 6h to dry it into a white solid, and then grind it into a white powder in a mortar; c. Place the white powder in a quartz boat, push the quartz boat into the central constant temperature zone of the tubular resistance furnace, introduce H2:N2 mixed gas for high temperature annealing, and obtain a reddish brown powder, wherein the temperature is set as follows: the tubular resistance furnace is heated from room temperature to 1050°C to 1100°C, the heating time is 60min to 100min, and maintained at this temperature for 30 to 120min; then naturally cooled to 200 to 650°C, the cooling time is 2h to 3h, and the quartz boat is pulled out; d. Use a ball mill to finely grind the reddish-brown powder to obtain silicon nanocrystalline fine powder. The ball milling parameters are set as follows: speed 400 to 700 rpm, duration 4 to 15 h; e. Add 25 to 60 mL of a mixed solution of deionized water, anhydrous ethanol and 49% hydrofluoric acid in a volume ratio of 1:1:1 to 1:1:4 to the silicon nanocrystal fine powder, and stir continuously at room temperature to etch the silicon nanocrystals and reduce the size of the silicon nanocrystals; f. Add 10 to 20 mL of a mixed solution of 1-dodecene and mesitylene in a volume ratio of 3:8 to 5:8 to the etched silicon nanocrystal powder, and perform hydrosilylation in an argon environment to obtain a clear yellow solution at a temperature of 160 to 180° C. for 1 to 4 h; g. Use anhydrous ethanol and methanol to wash away the residual 1-dodecene and trimethylbenzene in the clear yellow solution, and add n-pentane to obtain a uniformly dispersed silicon quantum dot colloid.
4. The preparation method according to claim 1, characterized in that: The operation of spin coating the erbium-doped HSQ mixed sol in step (3) is as follows: take 100 μL to 150 μL of the erbium-doped HSQ mixed sol, and set the spin coating parameters as follows: the first stage speed is 300 to 600 rpm, and the duration is 2 to 5 s; the second stage speed is 2000 to 4000 rpm, and the duration is 5 to 15 s.
5. The preparation method according to claim 1, characterized in that: In step (4), the erbium-doped HSQ film is placed on a constant temperature drying machine for heating and curing, the temperature of the constant temperature drying machine is 60-150° C., and the time is 5-20 minutes.
6. The preparation method according to claim 1, characterized in that: The H2 content in the mixed gas used in step (5) is 1% to 10%.
Citation Information
Patent Citations
Erbium silicate with sensitization effect as well as preparation method and application of erbium silicate
CN104787773A
Quantum dots based luminescent solar concentrator based on spectral up-conversion technique, flat concentrating photovoltaic device and preparation method thereof
CN110246922A
Erbium-doped silicon quantum dot crystal material as well as preparation method and application thereof
CN115926778A
Silicon quantum dot precursor, silicon quantum dot, LED device using silicon quantum dot, method for manufacturing silicon quantum dot precursor, method for manufacturing silicon quantum dot, and method for manufacturing LED device using silicon quantum dot
JP2024059064A
Energy Transferable Erbium doped Silica and its makingmethod
KR1020040098724A